Schottky junction ternary composite photocatalyst as well as preparation method and application thereof

By constructing a composite photocatalyst RF/EA-Fe/Ti3C2 MXene with Schottky-type heterojunction, the problems of poor photoresponsiveness and low catalytic efficiency of traditional metal oxide catalysts are solved, and more efficient photocatalytic oxidation performance is achieved.

CN119608195APending Publication Date: 2025-03-14ZHEJIANG GONGSHANG UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311175093.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Traditional metal oxide catalysts have problems in photocatalysis with poor photoresponsiveness and low catalytic efficiency, especially in terms of oxidation capacity.

Method used

By constructing a Schottky-type heterojunction, combining RF, EA-Fe and Ti3C2 MXene materials, the composite photocatalyst RF/EA-Fe/Ti3C2 MXene is formed, and hydrogen peroxide is generated in situ by resorcinol-formaldehyde resin, hydrothermal carbon and modified carbon nitride and other materials to improve oxidation performance.

Benefits of technology

The oxidation performance of the photocatalyst is significantly improved, the oxidation efficiency of tetracycline hydrochloride is enhanced, and the process conditions are mild, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004445253490000101
    Figure BDA0004445253490000101
  • Figure HDA0004445253560000011
    Figure HDA0004445253560000011
  • Figure HDA0004445253560000012
    Figure HDA0004445253560000012
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a Schottky junction ternary composite photocatalyst. The preparation method comprises the following steps: (1) respectively preparing RF powder, an EA-Fe solution and a Ti3C2MXene aqueous solution; and (2) mixing the RF powder, an EA-Fe solution and a Ti3C2MXene aqueous solution in proportion, and reacting in a dark place. The Schottky junction ternary composite photocatalyst is added into waste water containing tetracycline hydrochloride, after dark reaction adsorption equilibrium, visible light irradiation is carried out, and photocatalytic degradation is started. The RF / EA-Fe / Ti3C2-MXene composite photocatalytic material is prepared under the conditions of normal temperature and normal pressure, the conditions are mild, the mass proportion can be accurately controlled, and the RF / EA-Fe / Ti3C2-MXene composite photocatalytic material is suitable for large-scale production; and (4) the prepared composite material has the advantages of high catalytic activity, convenience in Schottky junction construction, low cost, multi-functionalization and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photocatalyst technology, and in particular to a RF / EA-Fe / Ti3C2 MXene photocatalyst and a preparation method and application thereof. Background Art

[0002] Refractory organic pollutants are extremely threatening to organisms due to their complex composition, toxicity, and the fact that they are easily combined with metal ions to form refractory composite pollutants. Antibiotic pollution can cause changes in the structure of microbial communities in water bodies, affect the ecological environment of water bodies, increase the number of harmful microorganisms in water bodies, increase harmful substances in water bodies, and affect human health. It can also lead to the continuous enhancement of environmental bacterial resistance and the production of super bacteria, which seriously endangers the medical and health fields.

[0003] As a green clean technology, photocatalysis uses the redox property of electron-hole pairs generated under light to treat heavy metals and organic pollutants. However, traditional metal oxide catalysts often have problems such as poor light response and low catalytic efficiency, and there is an urgent need to develop new and efficient visible light catalysts. Heterostructure construction is a common method to broaden the light absorption range of materials and improve the migration ability of photogenerated carriers. For example, the construction of heterojunctions such as Schottky heterojunction, crystal face junction, van der Waals heterojunction, S-type heterojunction and Z-type heterojunction can effectively improve the photocatalytic efficiency of photocatalysts. However, the oxidative active radicals of a single Schottky junction binary composite material are often dominated by holes, and the oxidation capacity needs to be improved. Summary of the invention

[0004] The present application provides a Schottky junction ternary composite photocatalyst and its preparation method and application. By introducing materials such as resorcinol-formaldehyde resin, hydrothermal carbon, and modified carbon nitride that generate hydrogen peroxide in situ under light, the composite system can produce hydroxyl and superoxide radicals with stronger oxidation ability, thereby further improving the oxidation performance.

[0005] Metal-organic complexes (MOCs) are new crystalline materials constructed by metal-organic coordination. Since they are metal ions coordinated by organic ligands of zero-dimensional or mononuclear configuration, they form three-dimensional materials by stacking. Therefore, the function of MOCs can be directional regulated by replacing, adjusting or modifying metal ions or organic ligands. At present, MOCs have made certain research progress in the field of photocatalysis. For example, thiosemicarbazide (TSCs) metal complexes, Schiff base metal complexes, triphenylamine functionalized bithiazole cobalt complexes, etc. have been proven to have good photocatalytic properties.

[0006] Ellagic acid (EA) is a dimeric derivative of gallic acid, which is widely found in various fruits and nuts. As a phenolic organic compound, it is easy to react with Ce 3+ 、Co 2+ , Cu 2+ , Fe 2+ , Fe 3+ ,La 3+ The metal cations such as ellagic acid and Fe chelate to form metal organic complexes, and strong chelating phenolic compounds often have good near-infrared absorption properties. 3+ After ionic bond coordination, the metal organic complex EA-Fe has a weak oxidation ability. Therefore, the present application considers improving the carrier separation and migration efficiency and the oxidation performance by constructing a Schottky type heterojunction method.

[0007] This application adopts a one-pot preparation method, using RF-generated hydrogen peroxide and EA-Fe to form an in-situ Fenton-like system, and introducing Ti3C2 MXene as a modifier to construct a Schottky junction with EA-Fe to prepare a new photocatalyst RF / EA-Fe / Ti3C2 MXene; at the same time, the ratio of Ti3C2 MXene can be adjusted, and the material is used for the photocatalytic oxidation of tetracycline hydrochloride (TC). The visible light catalytic performance test shows that when RF, Ti3C2 MXene and EA-Fe are constructed, the prepared ternary composite catalyst has a significantly better oxidation efficiency for TC than RF, EA-Fe and Ti3C2 MXene.

[0008] First, the present application provides a method for preparing a Schottky junction ternary composite photocatalyst, comprising:

[0009] (1) Prepare RF powder, EA-Fe solution and Ti3C2 MXene aqueous solution respectively;

[0010] The preparation of the RF powder comprises: mixing resorcinol, ammonia water and formaldehyde to form a colloidal suspension, then subjecting the colloidal suspension to heat treatment, and sequentially separating, washing, drying and grinding the reaction liquid obtained by the heat treatment to obtain the RF powder;

[0011] The preparation of EA-Fe solution comprises: adding ellagic acid ethanol solution dropwise to FeCl3 aqueous solution, mixing and reacting;

[0012] The preparation of Ti3C2 MXene aqueous solution comprises: dispersing Ti3AlC2 in a mixed solution of HCl and LiF for a mixed reaction, and after the mixed reaction is completed, the obtained product is washed and then redispersed in deionized water to obtain the Ti3C2MXene aqueous solution;

[0013] (2) Mix RF powder, EA-Fe solution and Ti3C2 MXene aqueous solution according to the ratio and react in the dark to obtain the product.

[0014] The preparation process of this application is relatively simple and the reaction conditions of the preparation process are relatively mild. The obtained composite photocatalyst material is RF / EA-Fe / Ti3C2 MXene. Unlike the single EA-Fe catalyst, EA-Fe as a MOCs material has good light absorption ability, but it has the problem of weak composite oxidation ability of photogenerated carriers. Because its conduction band and valence band match those of RF, and the Fe contained in it 2+ It can effectively activate the hydrogen peroxide generated under RF light, successfully construct an in-situ Fenton-like and type II heterojunction composite system, and effectively improve the separation efficiency of photogenerated carriers. In addition, the introduction of Mxene material and EA-Fe to construct a Schottky heterojunction further promotes the migration ability of carriers. Thereby effectively improving the efficiency of photocatalytic oxidation of TC, and by controlling the experimental parameter conditions, the optimal amount of Mxene added is obtained. The composite photocatalyst prepared in this application has the advantages of high catalytic activity and convenient synthesis.

[0015] Preparation of RF powder:

[0016] Optionally, the mass volume ratio of resorcinol, ammonia water and formaldehyde is 0.396g:40mL:0.5ml.

[0017] Optionally, the ammonia water is deionized water containing NH3·H2O; the concentration is calculated by adding 116 μL NH3·H2O to deionized water.

[0018] Optionally, the heat treatment conditions are: heating at 200°C for 24 hours.

[0019] Optionally, the drying condition is: vacuum drying at 60°C for 12h.

[0020] Preparation of EA-Fe solution:

[0021] Optionally, the concentration of the ethanol solution of ellagic acid is 1-1.2 g / mL (preferably 1.017 g / mL); the concentration of the FeCl3 aqueous solution is 0.05-0.08 g / mL (preferably 0.0535 g dissolved in 90 mL of deionized water); the volume ratio of the ethanol solution of ellagic acid to the FeCl3 aqueous solution is 1:8-10 (preferably 1:9).

[0022] Optionally, the ethanol solution of ellagic acid is prepared by dissolving ellagic acid in anhydrous ethanol.

[0023] Optionally, the stirring reaction time of the ethanol solution of ellagic acid and the FeCl3 aqueous solution is 3 to 24 hours.

[0024] Preparation of Ti3C2 MXene aqueous solution:

[0025] Optionally, the ratio of Ti3AlC2 dispersed in the mixed solution of HCl and LiF is 2g Ti3AlC2: 33.33mL HCl: 3g LiF; optionally, the mass percentage concentration of the HCl is 36%.

[0026] Optionally, the mixture is stirred magnetically for 12 to 36 hours.

[0027] Optionally, the washing treatment is: washing the above product with deionized water, centrifuging (10000rmin -1 , 5min) until the pH value of the supernatant is 5-6; then the solution is ultrasonicated for 5min and centrifuged (3500r min -1 , 15 min), the upper suspension was placed in a glass bottle, concentrated with 1 M NaOH, and then centrifuged.

[0028] Optionally, in step (2), the ratio of the ethanol solution of ellagic acid to the aqueous solution of FeCl3 in the preparation of the EA-Fe solution is 1:0.25 to 1:4; the concentration of the aqueous solution of Ti3C2 MXene is 0.5 to 1.5 g L -1 ; The mass volume ratio of RF powder, EA-Fe solution and Ti3C2 MXene aqueous solution is 2~8mgRF:100mLEA-Fe:2~8mLTi3C2 MXene aqueous solution.

[0029] Most preferably, in the preparation of the EA-Fe solution, the ratio of the ethanol solution of ellagic acid to the aqueous solution of FeCl3 is 1.9:1 (molar ratio is 1:1) for the mass ratio of ellagic acid to FeCl3; the concentration of the aqueous solution of Ti3C2 MXene is 0.8 g L -1 ; The mass volume ratio of the RF powder, EA-Fe solution and Ti3C2 MXene aqueous solution is 6 mg: 100 mL EA-Fe: 3.88 mL Ti3C2 MXene aqueous solution.

[0030] Optionally, in step (2), the light-proof reaction time is 10 to 15 hours.

[0031] The present application also provides a Schottky junction ternary composite photocatalyst prepared by the preparation method.

[0032] The present application also provides an application of the Schottky junction ternary composite photocatalyst in photocatalytic treatment of tetracycline hydrochloride-containing wastewater.

[0033] The present application also provides a method for degrading tetracycline hydrochloride in wastewater, comprising:

[0034] The Schottky junction ternary composite photocatalyst was added into the wastewater containing tetracycline hydrochloride, and after dark reaction to adsorption equilibrium, it was irradiated with visible light to start photocatalytic degradation.

[0035] Optionally, the added amount of the Schottky junction ternary composite photocatalyst is 0.01 to 0.5 g / L.

[0036] Optionally, the concentration of tetracycline hydrochloride in the wastewater is 10 to 30 mg / L.

[0037] Optionally, the visible light irradiation time is 2 to 4 hours.

[0038] Optionally, the pH of the wastewater is 2-5.

[0039] Compared with the prior art, the present invention has at least one of the following beneficial effects:

[0040] (1) The RF / EA-Fe / Ti3C2 MXene composite photocatalytic material was prepared under normal temperature and pressure conditions. The conditions are mild and the mass ratio can be precisely controlled, which is more suitable for large-scale production.

[0041] (2) The photocatalytic effect of the prepared RF / EA-Fe / Ti3C2 MXene composite photocatalytic material can be controlled by controlling the amount of incorporated RF and Ti3C2 MXene.

[0042] (3) Different from the single materials of RF and EA-Fe, the RF / EA-Fe / Ti3C2 MXene prepared in this application constructs a Schottky junction with the introduction of two-dimensional MXene materials, so that its photogenerated carriers can be rapidly migrated and converted. Since the conduction band and valence band of RF match the conduction band and valence band of EA-Fe, a type II heterojunction can be formed, which can give full play to the synergistic effect of the three in photocatalysis, thereby effectively improving the efficiency of photocatalytic degradation of TC.

[0043] (4) The composite material prepared in this application has the advantages of high catalytic activity, convenient construction of Schottky junction, low cost, and multifunctionality. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a comparison of the photocatalytic oxidation TC performance of RF / EA-Fe prepared with different RF ratios in Example 2 of the present application.

[0045] Figure 2 This is a comparison of the photocatalytic oxidation TC performance of RF / EA-Fe / Ti3C2MXene prepared with different proportions of Ti3C2 MXene in Example 3 of the present application.

[0046] Figure 3 This is a comparison of the photocatalytic oxidation rates of TC using different catalysts in Example 4 of the present application.

[0047] Figure 4 To optimize the cyclic stability of the prepared RF / EA-Fe / Ti3C2 MXene for treating TC-containing wastewater. DETAILED DESCRIPTION

[0048] The technical solution of the present application will be described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0050] The raw materials used in the following examples can all be obtained through commercial routes.

[0051] Example 1: Preparation of EA-Fe

[0052] 0.33mmol (0.0535g) FeCl3 was dissolved in 90mL deionized water to obtain FeCl3 aqueous solution; 0.1017g EA (ellagic acid) was dissolved in anhydrous ethanol (10mL) to obtain EA ethanol solution; 10mL EA ethanol solution was slowly dripped into 90mL FeCl3 aqueous solution under stirring; a dark blue solution was obtained after stirring for 12h in the dark; the powder was collected after centrifugation and washed with deionized water for several times. The obtained precipitate was dried under vacuum at 60℃ for 12h, and EA-Fe material was obtained after grinding, which was named E.

[0053] Example 2: Preparation of RF / EA-Fe

[0054] 1) Preparation of RF

[0055] Resorcinol (0.396 g) was added to deionized water (40 mL) containing 116 μL NH3·H2O and stirred for 30 min, and then 0.5 mL formaldehyde was added and stirred for 30 min to form a colloidal suspension; the solution was transferred to an 80 mL stainless steel autoclave lined with polytetrafluoroethylene and heated at 200°C for 24 h; the formed powder was precipitated by centrifugation and washed three times with acetone and deionized water respectively, and vacuum dried at 60°C for 12 h. RF was obtained after grinding and named R.

[0056] 2) Preparation of RF / EA-Fe

[0057] 0.33mmol (0.0535g) FeCl3 was dissolved in 90mL deionized water to obtain an aqueous FeCl3 solution; another 0.1017g EA was dissolved in anhydrous ethanol (10mL) to obtain an ethanol solution of EA; under stirring, 10mL EA ethanol solution was slowly dripped into the FeCl3 aqueous solution; 6mg RF (prepared in the previous step) was added to the mixed solution; after stirring for 12h in the dark, a dark blue solution was obtained, the powder was collected and washed with deionized water; the obtained precipitate was dried under vacuum at 60°C for 12h, and RF / EA-Fe was obtained after grinding, which was recorded as RE.

[0058] In this step, other conditions remain unchanged and the amount of RF added is changed, that is, 2 mg, 4 mg, 6 mg, and 8 mg of RF powder are added respectively to prepare RF / EA-Fe with different RF loading ratios, which are named RE-1, RE-2, RE-3, and RE-4 respectively.

[0059] 3) Photocatalytic oxidation TC performance test

[0060] Take 30 mg of RF / EA-Fe with different RF loading ratios (prepared in the previous step) and add it to 20 mg L -1 TC solution (100 mL). After 30 minutes of dark reaction under magnetic stirring, the LED light source was turned on for photocatalytic reaction; after 180 minutes of illumination, sampling was performed, centrifugal separation was performed, and the peak value of the supernatant was measured by liquid chromatography. By comparing the peak value before and after the reaction, the TC oxidation rate can be calculated.

[0061] The results are as follows Figure 1 As shown by Figure 1 It can be seen that RE-3 prepared by initially adding 6 mg RF exhibits the best photocatalytic performance.

[0062] Example 3: Preparation of RF / EA-Fe / Ti3C2 MXene

[0063] 1) Preparation of Ti3C2 MXene

[0064] 2g Ti3AlC2 was added to a mixed solution of 33.33mL HCl (36%) and 3g LiF and stirred for 36h. After the reaction, the product was washed with deionized water and centrifuged (10000r min -1 , 5min) until the pH value of the supernatant is 5-6; then the solution is ultrasonicated for 5min and centrifuged (3500r min -1, 15min), put the upper suspension into a glass bottle; and concentrate it with 1M NaOH. After centrifugation, the precipitate was re-dispersed with deionized water to obtain Ti3C2 MXene suspension (dispersion concentration was 0.8g L -1 ), kept in liquid form, named M.

[0065] Take 20mL of Ti3C2 MXene suspension, filter it, and freeze-dry the filtered membrane. The freeze-dried MXene membrane will fall off by itself, and weigh it to get xg to get the concentration of Ti3C2 MXene suspension.

[0066] 2) Preparation of RF / EA-Fe / Ti3C2 MXene

[0067] 0.33mmol (0.0535g) FeCl3 was dissolved in 90mL deionized water to obtain FeCl3 aqueous solution; 0.1017g EA was dissolved in anhydrous ethanol (10mL) to obtain EA ethanol solution; 10mL EA ethanol solution was slowly dripped into the FeCl3 aqueous solution under stirring; 6mg RF powder (prepared in Example 2) and 3.88mL 0.8g L were added to the mixed solution. -1 Ti3C2MXene aqueous solution (prepared in the previous step of this embodiment); after stirring for 12 hours in the dark, a dark blue solution was obtained, and the powder was collected and washed with deionized water; the obtained precipitate was dried under vacuum at 60°C for 12 hours, and RF / EA-Fe / Ti3C2MXene was obtained after grinding, which was recorded as REM.

[0068] In this step, other conditions remained unchanged, and the amount of Ti3C2 MXene aqueous solution added was adjusted, that is, 1.94, 3.88, 5.82, and 7.76 mL of 0.8 g L -1 Ti3C2 MXene solution, and the obtained RF / EA-Fe / Ti3C2MXene catalysts were named REM-1, REM-2, REM-3 and REM-4, respectively.

[0069] 3) Photocatalytic oxidation TC performance test

[0070] Take 30 mg of RF / EA-Fe / Ti3C2 MXene with different Ti3C2 MXene loading ratios (prepared in the previous step of this example) and add it to 20 mg L -1 TC solution (100 mL); under magnetic stirring conditions, after 30 minutes of dark reaction, turn on the LED light source for photocatalytic reaction. After 180 minutes of illumination, take a sample, centrifuge, take the supernatant and measure its peak value by liquid chromatography. By comparing the peak value before and after the reaction, the TC oxidation rate can be calculated.

[0071] The results are as follows Figure 2 As shown by Figure 2 It can be seen that the initial addition is 3.88mL 0.8g L -1 RF / EA-Fe / Ti3C2 MXene (REM-2) prepared from Ti3C2 MXene exhibits the best photocatalytic performance.

[0072] Example 4: Preparation of other control group catalysts

[0073] 1) Preparation of EA-Fe / Ti3C2 MXene

[0074] 0.33mmol (0.0535g) FeCl3 was dissolved in 90mL deionized water to obtain FeCl3 aqueous solution; 0.1017g EA was dissolved in anhydrous ethanol (10mL) to obtain EA ethanol solution; 10mL EA ethanol solution was slowly dripped into the FeCl3 aqueous solution under stirring; 3.88mL 0.8g L was added to the mixed solution -1 Ti3C2 MXene aqueous solution (prepared in the same manner as in Example 3); after stirring for 12 h in the dark, a dark blue solution was obtained, and the powder was collected and washed with deionized water; the obtained precipitate was dried under vacuum at 60°C for 12 h, and EA-Fe / Ti3C2 MXene was obtained after grinding, which was named EM.

[0075] 2) Preparation of RF / Ti3C2 MXene

[0076] 100 mg RF (prepared in Example 2) was dispersed in aqueous solution, and 3.88 mL 0.8 g L -1 Ti3C2MXene aqueous solution (prepared in the same manner as in Example 3); after stirring for 12 h in the dark, the powder was collected and washed with deionized water; the resulting precipitate was dried under vacuum at 60°C for 12 h, and ground to obtain RF / Ti3C2MXene, named RM.

[0077] 3) Photocatalytic oxidation TC performance test

[0078] Take 30 mg of different catalysts and add them to 20 mg L -1 TC solution (100 mL). After 30 minutes of dark reaction under magnetic stirring, the LED light source was turned on for photocatalytic reaction; after 180 minutes of illumination, sampling was performed, centrifugal separation was performed, and the peak value of the supernatant was measured by liquid chromatography. By comparing the peak value before and after the reaction, the TC oxidation rate can be calculated.

[0079] The results are as follows Figure 3 As shown, Figure 3 The corresponding relationship between the codes of the horizontal coordinates is shown in Table 1:

[0080] Table 1

[0081]

[0082] Depend on Figure 3 It can be seen that the initial addition of 6 mg RF and 3.88 mL 0.8 g L -1 RF / EA-Fe / Ti3C2 MXene (REM-2) prepared from Ti3C2 MXene exhibits the best photocatalytic performance.

[0083] Example 5: Cyclic Stability

[0084] The optimized RF / EA-Fe / Ti3C2 MXene (REM-2) was used as the photocatalyst for photocatalytic oxidation of TC for three cycles. Before each cycle, the photocatalyst was centrifuged, washed, dried, and then placed in a new 20 mg L -1 TC (100mL) solution was placed in a dark reaction under magnetic stirring for 30 minutes, and then the LED light source was turned on for photocatalytic reaction. After 180 minutes of illumination, samples were taken, centrifuged, and the supernatant was measured by liquid chromatography for its peak value. By comparing the peak values ​​before and after the reaction, the TC oxidation rate can be calculated. The results are shown in Figure 4 As shown in the figure, RF / EA-Fe / Ti3C2 MXene has good recycling stability, and its activity does not change significantly after three cycles.

[0085] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a Schottky junction ternary composite photocatalyst, characterized in that: include: (1) Prepare RF powder, EA-Fe solution and Ti3C2 MXene aqueous solution respectively; The preparation of the RF powder comprises: mixing resorcinol, ammonia water and formaldehyde to form a colloidal suspension, then subjecting the colloidal suspension to heat treatment, and sequentially separating, washing, drying and grinding the reaction liquid obtained by the heat treatment to obtain the RF powder; The preparation of EA-Fe solution comprises: adding ellagic acid ethanol solution dropwise to FeCl3 aqueous solution, mixing and reacting; The preparation of Ti3C2 MXene aqueous solution comprises: dispersing Ti3AlC2 in a mixed solution of HCl and LiF for a mixing reaction, and after the mixing reaction is completed, washing the obtained product and then redispersing it in deionized water to obtain the Ti3C2 MXene aqueous solution; (2) Mix RF powder, EA-Fe solution and Ti3C2 MXene aqueous solution according to the ratio and react in the dark to obtain the product.

2. The preparation method according to claim 1, characterized in that: In the preparation of the EA-Fe solution, the ratio of the ethanol solution of ellagic acid to the aqueous solution of FeCl3 is 1:0.25 to 1:

4. The concentration of the Ti3C2 MXene aqueous solution is 0.5 to 1.5 g L -1 ; The mass volume ratio of RF powder, EA-Fe solution and Ti3C2 MXene aqueous solution is 2~8mgRF:100mLEA-Fe:2~8mLTi3C2 MXene aqueous solution.

3. The preparation method according to claim 1, characterized in that: The light-proof reaction time is 10 to 15 hours.

4. A Schottky junction ternary composite photocatalyst prepared by the preparation method according to any one of claims 1 to 3.

5. Use of the Schottky junction ternary composite photocatalyst as claimed in claim 4 in photocatalytic treatment of wastewater containing tetracycline hydrochloride.

6. A method for degrading tetracycline hydrochloride in wastewater, characterized in that: include: The Schottky junction ternary composite photocatalyst according to claim 4 is added into wastewater containing tetracycline hydrochloride, and after dark reaction to adsorption equilibrium, visible light irradiation is performed to perform photocatalytic degradation.

7. The method according to claim 6, characterized in that The added amount of the Schottky junction ternary composite photocatalyst is 0.01-0.5 g / L.

8. The method according to claim 6, characterized in that The concentration of tetracycline hydrochloride in the wastewater is 10-30 mg / L -1 .

9. The method according to claim 6, characterized in that The visible light irradiation time is 2 to 4 hours.

Citation Information

Cited By

  • Iron-based metal-organic complex catalyst, preparation method and method for removing ofloxacin in water body

    CN120394094A

  • Iron-based metal-organic complex catalysts, their preparation methods, and methods for removing ofloxacin from water.

    CN120394094B